High levels of brain-type creatine kinase activity in human platelets and leukocytes: a genetic anomaly with autosomal dominant inheritance - Arnold, Heidwolf; Kemp, Katharina; Bugert, Peter (Blood cells, molecules & diseases, 2012)
The ectopic expression in peripheral blood cells of the brain-type creatine kinase (CKB) is an autosomal dominant inherited anomaly named CKBE (MIM ID 123270). Here, we characterized the CK activity in serum, platelets (PLT) and leukocytes (WBC) of 22 probands (from 8 unrelated families) and 10 controls. CK activity was measured by standard UV-photometry. Expression of the CKB gene was analyzed by real-time PCR and Western blotting. DNA sequencing including bisulfite treatment was used for molecular analysis of the CKB gene. Serum CK levels were comparable between probands and controls. CKBE probands revealed significantly higher CK activity in PLT (3.7 ± 2.7 versus 179.2 ± 83.0 U/10(12) PLT; p<0.001) and WBC (0.4 ± 0.3 versus 2.6 ± 2.1 U/10(9) WBC; p=0.004). Inhibitory anti-CKM antibodies did not affect CK activity indicating that the CK activity is generated exclusively by the CK-BB isoenzyme. CKB mRNA and protein levels were significantly higher in PLT and WBC from probands compared to controls. Re-sequencing of the entire CKB gene and methylation analysis of a CpG island revealed no alteration in CKBE probands. The genetic basis of CKBE remains unclear, however, we propose that a de-methylated CKB gene is inherited that leads to high CKB expression levels in myeloic precursor cells in the bone marrow.